Pengaruh Harga dan Promosi Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Intervening - Ibrahim, Sabina Natania; Arsyad, Annisa Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to determine whether there is an effect of price and promotion on customer loyalty through customer satisfaction on Indosat Ooredoo cellular card users in Samarinda City. This study uses a quantitative method by collecting data by distributing questionnaires to respondents. The study was conducted on 100 respondents who are active Indosat Ooredoo cellular card users aged 15-45 years who live in Samarinda City. The sampling technique used in this study is non-probability sampling with an online purposive sampling method. The collected data was then processed using the SmartPLS 4.1.0.9 analysis tool with the Structural Equation Modeling (SEM)-PLS method. The results of the study indicate that price and promotion have a positive and significant effect on customer satisfaction, price has a positive but insignificant effect on customer loyalty, promotion and customer satisfaction has a positive and significant effect on customer loyalty. Based on the results of the specific indirect effect, customer satisfaction successfully mediates positively and significantly the effect of price and promotion on customer loyalty.